CTL-Based “Lelempa Bokayong” Game Improves Addition Concept Understanding in Elementary School Students - Indri; Muh. Khaerul Ummah BK; Moh. Rudini (Madako Elementary School, 2026)
The low understanding of the concept of summation in elementary school students is still a fundamental problem in mathematics learning, especially due to approaches that tend to be abstract and do not relate to students' real experiences. This requires more contextual learning innovations, one of which is through the integration of traditional games in the CTL approach. This study aims to test the effectiveness of the integration of the traditional game “Lelempa Bokayong” in improving the understanding of the concept of summation in students of SDN 3 Dadakitan. The study used a pre-experimental design with a pre-test and post-test one group model, involving 7 class I students who were selected purposively from a total of 65 students. Data was collected through learning outcome tests and observations, then analyzed using the Wilcoxon Signed Rank Test. The results showed an increase in the average score from 48.71 to 66.42. The hypothesis test yielded a significance value of 0.043 (<0.05), which indicates a significant influence. These findings suggest that traditional game-based CTL approaches are effective in improving understanding of the concept of summation. The implications of the study confirm the importance of utilizing local wisdom to create meaningful and interesting learning.